2015
DOI: 10.30684/etj.33.6a.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation The Quality of Raw and Treated Water for Number of Water Treatment Plants in Baghdad, Using a Water Quality Index

Abstract: Laboratory tests were conducted to evaluate the quality of drinking water on some water treatment plants in Baghdad (AlKarkh, Shark Dijla, AlWathba, and Alkramh), the samples taken from raw (Tigris River) and treated water. The measurements of some physical and chemical properties taken every month and for eight years in order to evaluate the drinking water quality and efficiency of these plants. The quality of drinking water was calculated by using Canadian model index (Canadian Council of Ministers of the En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Finally the results in table (2) pointed that the value of the Canadian water quality index that calculation depending on the chemical parameters only showed that the water quality according to the index was 42.69 %, which means the water quality was in the fifth category according to the Canadian classification, which also means that the water quality is poor, and the water quality is almost always threatened or impaired, and the conditions usually depart from natural or desirable levels, and these could be return to the low levels of the stream and the large number of evaporation processes because of high temperature [48], in addition to the increased discharge of wastes that consume oxygen and raise the pH [44]. All that can contribute to decrease the water quality index and pointed to reduce the value of water for direct human using and drinking.…”
Section: -2-chemical Parametersmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally the results in table (2) pointed that the value of the Canadian water quality index that calculation depending on the chemical parameters only showed that the water quality according to the index was 42.69 %, which means the water quality was in the fifth category according to the Canadian classification, which also means that the water quality is poor, and the water quality is almost always threatened or impaired, and the conditions usually depart from natural or desirable levels, and these could be return to the low levels of the stream and the large number of evaporation processes because of high temperature [48], in addition to the increased discharge of wastes that consume oxygen and raise the pH [44]. All that can contribute to decrease the water quality index and pointed to reduce the value of water for direct human using and drinking.…”
Section: -2-chemical Parametersmentioning
confidence: 97%
“…Table (2,4) showed average values of chemical parameters in three sites on Al-Mahawil stream, where the seasonal average of electrical conductivity (E.C.) were recorded higher concentration in summer (1257) us/cm in site (S2), and lower concentration (887) us/cm in winter in site (S1).…”
Section: -2-chemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation